Generalized Bifuzzy Lie Subalgebras. (30th December 2013) - Alshehri, Noura; Akram, Muhammad
Abstract : We introduce the concept of( γ, δ ) -bifuzzy Lie subalgebra, whereγ, δ are any two of ∈, q, ∈ ∨ q, ∈ ∧ q withγ ≠ ∈ ∧ q, by using belongs to relation( ∈ ) and quasi-coincidence with relation( q ) between bifuzzy points and bifuzzy sets and discuss some of its properties. Then we introduce bifuzzy soft Lie subalgebras and investigate some of their properties.